2019
DOI: 10.1021/acscatal.9b00780
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Asymmetric Michael Additions of Nitromethane to α,β-Unsaturated Aldehydes via Enzyme-bound Iminium Ion Intermediates

Abstract: The enzyme 4-oxalocrotonate tautomerase (4-OT) exploits an N-terminal proline as main catalytic residue to facilitate several promiscuous C–C bond-forming reactions via enzyme-bound enamine intermediates. Here we show that the active site of this enzyme can give rise to further synthetically useful catalytic promiscuity. Specifically, the F50A mutant of 4-OT was found to efficiently promote asymmetric Michael additions of nitromethane to various α,β-unsaturated aldehydes to give γ-nitroaldehydes, important pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 31 publications
(16 reference statements)
1
102
0
Order By: Relevance
“…Communications group is focused on further improving the peroxygenase activity of this promising cofactor-independent enzyme, making use of a recently developed selective colorimetric "turn-on" probe for efficient engineering of iminium biocatalysis. [13] The non-natural peroxygenase activity of 4-OT, together with its previously reported promiscuous CÀC bondforming Michaelase [7,9,14] and aldolase [15] activities, emphasize the chemical versatility of the 4-OT protein scaffold.…”
Section: Angewandte Chemiementioning
confidence: 92%
“…Communications group is focused on further improving the peroxygenase activity of this promising cofactor-independent enzyme, making use of a recently developed selective colorimetric "turn-on" probe for efficient engineering of iminium biocatalysis. [13] The non-natural peroxygenase activity of 4-OT, together with its previously reported promiscuous CÀC bondforming Michaelase [7,9,14] and aldolase [15] activities, emphasize the chemical versatility of the 4-OT protein scaffold.…”
Section: Angewandte Chemiementioning
confidence: 92%
“…[e] Determined by GC with chiral stationary phase or derivatized into a cyclic acetal and determined by HPLC with a chiral stationary phase. The absolute configuration was determined by comparison to literature . [f] Isolated yield compared to 6 .…”
Section: Resultsmentioning
confidence: 99%
“…4‐OT is unique in that it can use 5 as substrate for C−C bond‐forming Michael‐type additions to nitroolefin acceptors and for aldol condensations with benzaldehydes . Previously, we have demonstrated that 4‐OT can be combined with other biocatalysts and chemocatalysts to convert 6 and 8 into GABA analogues using two complementary one‐pot cascade reactions . However, both routes rely on 5 as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…7d). 115 Reduction of the intermediate iminium ion by sodium cyanoborohydride and subsequent mass spectrometry analysis provide evidence that supports the formation of the iminium intermediate. 73 Mutagenesis via a combined computational and experimental approach has led to the identication of enhanced variants.…”
Section: -Oxalocrotonate Tautomerasementioning
confidence: 88%